Simulation of assembly flow lines with buffer spaces - Liew, Kai Fong. (2010)
This report presents an interesting analytical approach in the operational research pertaining to two types of systems – asynchronous and synchronous – widely used in industrial manufacturing processes. It has been widely proven by many different mathematical models that asynchronous systems can be a highly effective industrial application. However, computer simulations to ascertain the accuracy of such formulas were hard to come by. Thus, this project will investigate some trends using computer simulation as opposed to the conventional mathematical methods studies.